N-asetil sisteinin kolistin nefrotoksisitesine karşı koruyucu etkilerinin araştırılması - Ercan, Çilem (My University, 2015)
THE PROTECTIVE EFFECTS OF N-ACETYLCYSTEINE AGAINST TO COLISTIN-INDUCED NEPHROTOXICITY Aim: The aim of the present study was to investigate the protective effects of N-acetylcysteine (NAC) prophylaxis and treatment on kidney functions in the colistin-induced nephrotoxicity in rats. Methods: Adult Wistar rats were divided into four groups (n = 7). Nephrotoxicity group was exposed to colistin by i.p. in a daily total dose at 300000 IU/kg body weight. NAC was administered to the treatment group by i.p. in a daily total dose at 300000 IU/kg body weight two hours before the colistin injection. The other group received only NAC by i.p. in a daily total dose at 300000 IU/kg body weight. The control group received 2 ml/kg body weight saline solution via the same route. The total daily doses of all injections were divided into 2 equal portions administered 8 hours apart, for 10 days. 24 hours after last injections, animals were sacrificed under anesthesia for biochemical and histopathological examinations, their intracardiac blood samples were collected and kidney tissues were removed. Results: Total histological activity score was significantly higher in colistin-induced nephrotoxicity group compared with other groups (p < 0.0001). Besides, the histopathological damage observed in the colistin group were significantly decreased in the NAC+colistin group treated with NAC. Accordingly, creatinine level which was very high in colistin group was significantly decreased in the NAC+colistin group when compared with colistin group (p < 0.01). The apoptotic cell numbers in NAC+colistin group were also significantly lower than those of colistin group (p<0.0001). Finally, by histopathological examination, a significant decrease in tubular necrosis by NAC treatment was observed as compared with colistin group. Conclusion: Our results suggest that NAC treatment may ameliorate the effects of colistin-induced functional and structural damage in kidney. Keywords: Apoptosis, colistin, creatinine, nephrotoxicity, N-acetylcysteine.
N-ASETİL SİSTEİNİN KOLİSTİN NEFROTOKSİSİTESİNE KARŞI KORUYUCU ETKİLERİNİN ARAŞTIRILMASI Amaç: Bu çalışmada kolistin nefrotoksisitesi oluşturulmuş sıçanlarda N-asetil sistein proflaksi ve tedavisinin böbrek fonksiyonları üzerine olan koruyucu etkisinin araştırılması amaçlandı. Yöntem: Erişkin Wistar erkek sıçanlar 4 gruba ayrıldı. Nefrotoksisite grubuna 300000 IU/kg/gün toplam doz olacak şekilde 8 saat arayla iki doza bölünerek intraperitonel (i.p.) yolla kolistin verildi. Tedavi grubuna 300000 IU/kg/gün toplam doz olacak şekilde 8 saat arayla iki doza bölünerek i.p. yolla N-asetil sistein (NAS) verildi. Yine bu gruba her bir NAS enjeksiyonundan 2 saat sonra 300000 IU/kg/gün toplam doz olacak şekilde kolistin uygulandı. Diğer bir gruba ise 300000 IU/kg/gün toplam doz olacak şekilde 8 saat arayla iki doza bölünerek i.p. yolla NAS verildi. Kontrol grubuna aynı yolla 2 ml (mililitre)/kg (kilogram) serum fizyolojik uygulandı. Tüm gruplara enjeksiyonlar 10 gün boyunca tekrarlandı. Son doz verildikten 24 saat sonra, biyokimyasal ve histopatolojik incelemeler için tüm hayvanların anestezi altında intrakardiyak kan örnekleri alınıp böbrek dokuları çıkartıldı. Bulgular: Kolistine bağlı nefrotoksisite oluşturulan grupta toplam histolojik aktivite skoru diğer gruplarla kıyaslandığında anlamlı derecede yüksek bulundu (p<0.0001). Diğer taraftan kolistin grubunda görülen histopatolojik belirtiler, NAS tedavisi uygulanan NAS+Kolistin grubunda istatistiksel olarak anlamlı bir şekilde azaldı. Buna göre, kreatinin düzeyleri kolistin grubunda artarken NAS+Kolistin grubunda kolistin grubuna göre istatistiksel olarak anlamlı bir şekilde azaldı (p<0.01). Kolistin grubunda artan apoptotik hücre sayısı NAS tedavisi uygulanan NAS+Kolistin grubunda istatistiksel olarak anlamlı derecede azaldı (p<0.0001). Histopatolojik incelemelerde tübüler nekrozun NAS+Kolistin grubunda kolistin grubuna oranla daha az olduğu gözlendi. Sonuç: Çalışmanın sonucunda, kolistinin böbrekte işlevsel ve yapısal hasarlara sebep olduğu, NAS tedavisinin ise bu hasarlara karşı iyileşme gösterdiği gözlenmiştir.
Keywords: Apoptozis = Apoptosis; Kolistin = Colistin; Kreatinin = Creatinine; N-asetilsistein = N-acetylcysteine; Nefrotoksisite = Nephrotoxicity